Bio-climatic Comfort and Climate Change Nexus: A Case Study in Burdur Basin - IŞINKARALAR, Öznur; IŞINKARALAR, Kaan; ŞEVİK, Hakan; KÜÇÜK, Ömer (Kastamonu University, 2023)
Aim of study: Climate change triggers many problems, such as loss of biodiversity on land and sea, destruction of forest areas, poverty, inequality, and economic development. One of the most vital indicators of quality of life and sustainable development is temperature, humidity, and wind conditions, which are in the range of bio-climatic comfort values. The changes in these parameters due to global warming threaten vitality and affect the use of space and quality of life in cities. The study aimed to model the evolution of bioclimatic comfort zones with the effect of climate change in the research area.
Area of study: The research was carried out in the Burdur Basin of Türkiye, which is an area that includes the underground and surface water bodies and the lakes region within its borders.
Material and Methods: Models were produced at 20-year intervals until 2100. The spatio-temporal variations are generated according to the IPCC's SSPs 245 and SSPs 585 scenarios. The discomfort index (DI) and Effective warming wind speed (ETv) were used to determine bioclimatic comfort.
Main Results: According to the DI, 87.4% of the area will be in the cold zone today, while in 2100, 50.5%, according to the SSP245, and 98.3%, according to the SSP 585 will be in the comfort zone. According to ETv, 92.7% of the area is quite cool today; by 2100, 90% of the site will be classified as slightly cool according to SSP 245, and 89.3%, according to SSP 585 will turn into mild areas.
Research highlights: The results of the research reflect the spatial impact of climate change and are significant in terms of holistic risk management at the basin scale
Keywords: 13. Climate action; 11. Sustainability; 1. No poverty; 15. Life on land; 6. Clean water; 12. Responsible consumption